Positive and negative interspecific interactions between coexisting rice planthoppers neutralise the effects of elevated temperatures - Horgan, Finbarr G.; Arida, Arriza; Ardestani, Goli; Almazan, Maria Liberty P. (Wiley, 2021)
Global warming is often predicted to increase damage to plants through direct effects on insect herbivores. However, the indirect impacts of rising temperatures on herbivores, mediated through interactions with their biotic environment, could dampen these effects. Using a series of reciprocal density experiments with gravid females and developing nymphs, we examined interspecific competition between two coexisting phloem feeders Nilaparvata lugens (BPH) and Sogatella furcifera (WBPH), on rice at 25 and 30°C. WBPH performed better (i.e. adults survived longer, nymphs developed faster and grew larger) at 25°C and BPH (i.e. nymphs developed faster) at 30°C. However, contrary to predictions, WBPH had a greater effect in reducing oviposition and nymph performance in BPH at 30°C. A decoupling of resource use by WBPH and its antagonistic effects on BPH at the higher temperature suggests that WBPH feeding induces host defences that reduce BPH fitness (i.e. interference competition). Meanwhile, BPH facilitated WBPH oviposition at 30°C and facilitated WBPH nymph performance at 25 and 30°C. Greater facilitation of feeding in WBPH nymphs by BPH at high densities suggests that mechanical damage and host responses to damage increased the fitness of the heterospecific nymphs. Although BPH also facilitated egg‐laying by WBPH, intra‐ and interspecific crowding countered this facilitation at both temperatures. Simulated life tables for planthoppers at 25 and 30°C depicted significantly lower offspring numbers on rice infested by WBPH alone and from mixed BPH‐WBPH infestations than from infestations by BPH alone. Our results indicate how interference competition—mediated through host plant defences—can increase ecosystem resilience to the warmer temperatures predicted under global climate change. A free Plain Language Summary can be found within the Supporting Information of this article.